Integrating R&D and marketing in new product development - Fain, Nuša (Strojniški vestnik, 2011)
R&D - marketing integration is considered to be a critical activity within New Product Development (NPD). A theoretical framework for the study of R&D - marketing integration levels developed by Gupta et al (1986) is one of the most widely cited R&D - marketing integration frameworks in scientific literature. It is based on the presumption that strategy, environmental, organizational and individual factors are those determining R&D - marketing integration levels and consequently NPD success. Several empirical studies have been conducted to test this framework, however most of them have dealt only with portions of Gupta et al (1986)'s model. This paper is an attempt to put forward and test an integrated research protocol for the study of R&D - marketing integration, based on this theoretical framework. Empirical evidence gained from a questionnaire survey and two company case studies show, that people active within the R&D - marketing interface perceive the studied constructs as relevant for R&D - marketing integration, thus giving confirmation to Gupta et al (1986)s model. The presented research protocol can therefore be considered as a valid start into R&D - marketing integration research within an integrated framework.
Keywords: integration; marketing; NPD; proces osvajanja izdelka; R and D; razvoj; teoretični okviri integracije; theoretical framework; trženje